A Comprehensive Study on the Onomastics of the South-Eastern Lake Onega Area. Review of: Sobolev, A. I. Russian Onomastics of Finno-Ugric Origin in the South-Eastern Obonezhye: Experience in the Reconstruction of Linguistic Interaction (Doctoral dissertation). Institute for Linguistic Studies of the RAS, St Petersburg, 2024. 446 p. - Anna Andreevna Bakhtereva (Вопросы ономастики, 2025)
This review discusses Anton I. Sobolev’s doctoral thesis Russian Onomastics of Finno-Ugric Origin in the Region of South-Eastern Obonezhye: The Experience of Language Interaction Reconstruction. The study is grounded in an extensive body of evidence, including data collected by the author through fieldwork and a wide range of archival sources. The South-Eastern Lake Onega region is particularly significant as a zone of long-term contact between three languages: Vepsian, Karelian, and Russian. The central hypothesis of the dissertation is that onomastic data, especially toponyms and anthroponyms, can serve as a primary basis for determining both the relative and absolute chronology of language use and interaction in substrate contexts. Drawing on a diverse set of materials — scribal and census books, archival documents, topographic maps and plans (18th–20th centuries), the toponymic card index of the Karelian Research Centre of the Russian Academy of Sciences, other publicly available toponymic databases, and the author’s own field data — the study also incorporates linguistic sources (primarily dialect dictionaries) and a broad spectrum of non-linguistic literature, including archaeological, geological, geographical, biological, ethnographic, and historical works related to the region. The author succeeds in reconstructing the geographical spread and chronological boundaries of Vepsian and Karelian language presence in the region, as well as the subsequent phases of Vepsian-Russian and Karelian-Russian contact. The study also recovers vocabulary units that are no longer attested in the modern Vepsian and Karelian languages. The overall evidence, including the widespread presence of substrate toponymy (semi-calques and calcified toponyms), substrate vocabulary (including calcified lexical items), and supporting data from historical, archaeological, ethnographic, and architectural sources, clearly supports the conclusion that the region experienced a gradual and extensive shift from Vepsian and Karelian to Russian.